Photonics Based Microwave Hybrid Coupler With Tunable Coupling Ratio and Phase Difference - Yanliang Zhang; Erwin H. W. Chan; Xudong Wang; Xinhuan Feng; Bai-Ou Guan (IEEE Photonics Journal)
A new microwave hybrid coupler that solves the problems of limited bandwidth and reconfigurability in conventional couplers, is presented. It is based on a bi-directional operating optical phase modulator and an optical signal processor to control the amplitude and phase of the phase modulated optical signals. The use of photonic technology enables the realization of a microwave hybrid coupler with wide coupling ratio and phase tuning ranges. The photonics-based microwave hybrid coupler also has a wide bandwidth, and a small amplitude and phase imbalance. Experimental results demonstrate that the microwave hybrid coupler exhibits 3 to 20 dB coupling ratio tuning and 0° to 360° phase tuning over a 3-dB operating frequency from 6 to 16 GHz.